An Outdoor Access Period Improves Chicken Cecal Microbiota and Potentially Increases Micronutrient Biosynthesis - Varriale, Lorena; Coretti, Lorena; Dipineto, Ludovico; Green, Brian D.; Pace, Antonino; Lembo, Francesca; Menna, Lucia Francesca; Fioretti, Alessandro; Borrelli, Luca (Frontiers in Veterinary Science, 2022)
Characterizing the gut microbiota of free-range and alternative poultry production systems provides information, which can be used to improve poultry welfare, performance and environmental sustainability. Gut microbiota influences not only host health and metabolism but also the presence of zoonotic agents contaminating food of animal origin. In the present study, composition and diversity of caecal microbiota community of free-range grown chickens was characterized by 16S rDNA high-throughput Illumina sequencing. Significant differences were observed in the composition of chicken caecal microbiota at the timepoints of 28 (Indoor) and 56 (Outdoor) days of age i.e., before and after the outdoor access period of chicken groups. The Outdoor group showed a richer and more complex microbial community, characterized by the onset of new phyla such as Deferribacterota and Synergistota, while Campylobacterota increased in Indoor. At species level, is noteworthy the occurrence of Mucispirillium schaedleri in Outdoor, that is known to potentially stimulate mucus layer formation in distal intestinal tract, thus being associated with healthy gut. We also report a significant decrease in the Outdoor group of Helicobacter pullorum, highlighting that the lower abundance at the age of slaughter reduced the possibility to contaminate chickens’ carcasses and consequently, its zoonotic potential. As revealed by a mutual exclusion study in network analysis, H. pullorum was present only if B. barnesiae, an Uncultured organism of genus Synergistes and Bacteroides gallinaceum were absent. Finally, microbiome predictive analysis revealed an increase of vitamins and other micronutrient biosynthesis such as queuosine (Q) and its precursor pre Q0, in the Outdoor group, suggesting that the outdoor evolved microbiota of chickens does contribute to the vitamin pool of the gut and the biosynthesis of micronutrients involved in vital cell processes.